PERCEPTION BY STUDENTS OF THE SPECIALTY OF "JOURNALISM" OF DISTANCE LEARNING AND ELECTRONIC EDUCATIONAL PUBLICATIONS IN THE INFORMATION AND EDUCATIONAL ENVIRONMENT OF A HIGHER EDUCATIONAL INSTITUTION - Nadiya Figol; Sergiy Tomilenko; Bogdan Figol (Інтегровані комунікації, 2025)
Distance learning has become a necessary element of modern education, especially in the context of the COVID-19 pandemic and Russia's military aggression against Ukraine. This process significantly changes traditional approaches to the educational process, requiring adaptation from both students and instructors.